KESTABILAN PENYETARAAN HORIZONTAL DENGAN METODE LINIER BERDASARKAN PROPORSI KELOMPOK GANDENG - Yustiandi, Yustiandi (Jurnal Evaluasi Pendidikan, 2018)
This study aims to determine the difference of stability of horizontal equiting of linear method with the 15%, 20%, 25%, and 30% anchor group and with 50 times replications. This research is done by analyzing the students’ physics learning scores. The population in this research is all high school students of grade 11 science program in Pandeglang District and the sample is students grade 11 in SMAN 1 Pandeglang, SMAN 2 Pandeglang, SMAN 4 Pandeglang, SMAN 6 Pandeglang, and SMAN CMBBS which amounts to 800 people taken simple random with replacement. The research method used is the experimental method by comparing the Root Mean Square Difference (RMSD) value of the equation based on the difference of the anchor group. The results showed that there was a difference of horizontal equiting stability with linear method with anchor group proportion 15%, 20%, 25%, and 30% with 50 times replications. Post hoc test are used to determine whether there are differences between groups if each group is compared. Based on post hoc test, it is known that the equating for the anchor group proportion 15% is most stable compared with the stability of equating for the anchor group proportion 20%, 25%, and 30% coupling with replication 50 times.